Experimental analysis of cold-formed steel channel and lipped-channel profiles connected to roof panel - R-Factor analysis - Javaroni, C. E.; Gonçalves, R. M.; Malite, M. (My University, 2002)
This paper presents and discusses test results of simulated suction effect due wind action on purlin-channel and lipped-channel sections carried out in a vacuum box. The chosen profile sections and their dimensions are those frequently used in steel construction in Brazil. The experimental results and the failure mode analysis of the purlin behaviour subjected to suction effect were compared with the theoretical analysis and R-factor for all load steps. The tests were carried out in a vacuum box with plan dimensions of 4 m × 6 m, where the suction effect due to wind was simulated. The air contained inside the vacuum box was gradually removed by a vacuum cleaner and the results of R-factors were obtained. A total of 15 channel and lipped-channel profiles of 5,740mm length were tested. The first series of tests was carried out without sag rods while the second purlin test was executed with two sag rods, also representing usual situations of those elements in the Brazilian steel construction. The steel panel had a trapezoidal section with 40mm height and 0.65 mm thickness, connected to the profiles using screws. They were measured vertical and horizontal displacements and strains in the middle section of the purlin. Those results allowed an evaluation of the strain and the R-Factor, as proposed by LaBoube (1992, 1991), during each load steps.